Entangled in the Forest of Brexit - Stallabrass, Julian (Design/Arts/Culture, 2023)
Epping Forest, once a royal hunting ground, known for its ancient oaks (symbols of England) lies on the outskirts of London. Now given over to the public, divided by roads and hemmed in by private property, it is a suburban woodland. Brexit—the vote to leave the European Union—sharply divided remainer London from the neighbouring county of Essex, which voted strongly to leave. The border between the two runs through the forest, sometimes following tracks and streams, and sometimes straying into dense thickets. For this photographic slide display, I followed it as best I could using map and compass, on a meandering and doubtless erratic path, looking for signs of social disaffection on the hinge of English county and global city.